Penegakan Hukum Terhadap Penyalahgunaan Narkotika Dikalangan Mahasiswa Di Tinjau Dari Undang-undang Nomor 35 Tahun 2009 Tentang Narkotika - Syireen Humaira; Dini Dewi Heniarti (Bandung Conference Series: Law Studies, 2024)
Abstract. Narcotics are a group of substances that generally have a risk of addiction for users if used continuously. Currently, the use of narcotics is often abused by society, especially students. Abuse in the use of narcotics refers to the use of drugs or dangerous substances for purposes other than medicinal purposes, and is carried out without following the instructions or prescribed dosage. Every year narcotics abuse always increases among teenagers and students. Data from the National Narcotics Agency (BNN) states that there has been an increase in the prevalence of drugs among pupils and students. In 2019, it was recorded at 1.1 percent, then increased to 1.38 percent in 2021. This research aims to find out the limits of narcotics abuse in view of Law Number 35 of 2009 concerning Narcotics regarding narcotics abuse among students and to find out about how the law is enforced by the authorities. law and higher education in preventing and dealing with narcotics abuse. This research uses a normative juridical approach with research specifications that are descriptive analysis. This research data was collected through a literature study using secondary data and the data analysis used was qualitative juridical. The results of this research indicate that the criminal act of narcotics abuse is activities related to narcotics without permission, control and supervision from authorized institutions, thereby violating statutory regulations. Narcotics abusers, including addict victims, are considered perpetrators of narcotics crimes which are only punished with imprisonment without considering the negative impacts. To prevent and overcome narcotics abuse among students, various efforts are needed from higher education institutions, such as the requirement for a Drug Free Certificate, outreach, cooperation and supervision. Law Number 35 of 2009 concerning Narcotics is expected to suppress the distribution and use of narcotics in Indonesia. Abstrak. Narkotika merupakan suatu kelompok zat yang umumnya mempunyai resiko untuk kecanduan bagi penggunanya bila digunakan secara terus menerus. Penggunaan narkotika pada saat ini sudah sering disalahgunakan oleh kalangan masyarakat terutama mahasiswa. Penyalahgunaan dalam penggunaan narkotika merujuk kepada penggunaan obat-obatan atau zat-zat berbahaya dengan maksud yang bukan untuk tujuan pengobatan, dan dilakukan tanpa mengikuti petunjuk atau dosis yang telah ditentukan. Setiap tahun penyalahgunaan narkotika selalu meningkat dikalangan remaja dan mahasiswa. Data dari Badan Narkotika Nasional (BNN) menyebutkan terjadi peningkatan prevalensi narkoba di kalangan pelajar dan mahasiswa. Pada 2019 tercatat 1,1 persen kemudian naik menjadi 1,38 persen di 2021. Penelitian ini bertujuan untuk mengetahui batasan penyalahgunaan narkotika dilihat dari Undang-undang Nomor 35 Tahun 2009 tentang Narkotika terhadap penyalahgunaan narkotika dikalangan mahasiswa serta untuk mengetahui tentang bagaimana penegakan hukum dari aparat hukum dan perguruan tinggi dalam mencegah dan menanggulangi penyalahgunaan narkotika. Penelitian ini menggunakan metode pendekatan yuridis normatif dengan spesifikasi penelitian bersifat deskriptif analisis. Data penelitian ini dikumpulkan secara studi kepustakaan/literatur dengan menggunakan data sekunder dan analisis data yang digunakan yaitu yuridis kualitatif. Hasil dari penelitian ini bahwa batasan tindak pidana penyalahgunaan narkotika ini merupakan kegiatan yang berkaitan dengan narkotika tanpa izin, pengendalian, dan pengawasan dari lembaga yang berwenang, sehingga melanggar peraturan perundang-undangan. Penyalahguna narkotika, termasuk korban pencandu, dianggap sebagai pelaku tindak pidana narkotika yang hanya dihukum dengan pidana penjara tanpa mempertimbangkan dampak negatifnya. Untuk mencegah dan menanggulangi penyalahgunaan narkotika di kalangan mahasiswa, diperlukan berbagai upaya dari pergutuan tinggi, seperti syarat Surat Keterangan Bebas Narkoba, sosialisasi, kerjasama, dan pengawasan. Undang-undang Nomor 35 Tahun 2009 tentang Narkotika diharapkan dapat menekan peredaran dan penggunaan narkotika di Indonesia. ABSTRACT Narcotics are a group of substances that generally have a risk of addiction for users if used continuously. Currently, the use of narcotics is often abused by society, especially students. Abuse in the use of narcotics refers to the use of drugs or dangerous substances for purposes other than medicinal purposes, and is carried out without following the instructions or prescribed dosage. Every year narcotics abuse always increases among teenagers and students. Data from the National Narcotics Agency (BNN) states that there has been an increase in the prevalence of drugs among pupils and students. In 2019, it was recorded at 1.1 percent, then increased to 1.38 percent in 2021. This research aims to find out the limits of narcotics abuse in view of Law Number 35 of 2009 concerning Narcotics regarding narcotics abuse among students and to find out about how the law is enforced by the authorities. law and higher education in preventing and dealing with narcotics abuse. This research uses a normative juridical approach with research specifications that are descriptive analysis. This research data was collected through a literature study using secondary data and the data analysis used was qualitative juridical. The results of this research indicate that the criminal act of narcotics abuse is activities related to narcotics without permission, control and supervision from authorized institutions, thereby violating statutory regulations. Narcotics abusers, including addict victims, are considered perpetrators of narcotics crimes which are only punished with imprisonment without considering the negative impacts. To prevent and overcome narcotics abuse among students, various efforts are needed from higher education institutions, such as the requirement for a Drug Free Certificate, outreach, cooperation and supervision. Law Number 35 of 2009 concerning Narcotics is expected to suppress the distribution and use of narcotics in Indonesia.